Chronic Bumetanide Infusion Alters Young Neuron Morphology in the Dentate Gyrus Without Affecting Contextual Fear Memory - Gómez-Correa, Gibrán; Zepeda, Angelica (Frontiers in Neuroscience, 2020)
Young neurons in the adult brain are key to some types of learning and memory. They integrate in the dentate gyrus (DG) contributing to such cognitive processes following timely developmental events. While experimentally impairing GABAergic transmission through the blockade or elimination of the ionic cotransporter NKCC1 leads to alterations in the proper maturation of young neurons, it is still unknown if the in vivo administration of common use diuretic drugs that block the cotransporter, alters the development of young hippocampal neurons and affects DG-related functions. In this study, we delivered chronically and intracerebroventricularly the NKCC1 blocker bumetanide to young-adult rats. We analyzed doublecortin density and development parameters (apical dendrite length and angle and dendritic arbor length) in doublecortin positive neurons from different subregions in the DG and evaluated the performance of animals in contextual fear learning and memory. Our results show that in bumetanide-treated subjects, doublecortin density is diminished in the infra and suprapyramidal blades of the DG; the length of primary dendrites is shortened in the infrapyramidal blade and; the growth angle of primary dendrites in the infrapyramidal blade is different from control animals. Behaviorally, treated animals showed the typical learning curve in a contextual fear task, and freezing-time displayed during contextual fear memory was not different from controls. Thus, in vivo icv delivery of bumetanide negatively alters DCX density associated to young neurons and its proper development but not to the extent of affecting a DG dependent task as aversive context learning and memory.